A Fatal Case of Relapsing Pneumonia Caused by Legionella pneumophila in a Patient with Rheumatoid Arthritis After Two Injections of Adalimumab. Issue 6 (January 2013) - Hayashi, Masatoshi; Kuraishi, Hiroshi; Masubuchi, Takeshi; Furihata, Kaneyuki; Aida, Yuka; Kobayakawa, Tomonori; Deguchi, Masao; Kojima, Toshihisa; Ishiguro, Naoki; Kanamono, Toshihisa
We present a rare fatal case of relapsing pneumonia caused by Legionella pneumophila in a patient with rheumatoid arthritis after only two injections of adalimumab. A 78-year-old Japanese woman with a 14-year history of rheumatoid arthritis was prescribed adalimumab because her disease activity remained high. However, 8 days after her second injection of adalimumab, she was admitted to our hospital and diagnosed with pneumonia caused by L. pneumophila . Following intravenous antibiotic therapy, she recovered completely from pneumonia and was discharged on day 10, but pneumonia relapsed, resulting in death 79 days after the first episode of pneumonia. L. pneumophila can lead to recurrence of pneumonia that can ultimately prove fatal, similar to the present case. A review of the pertinent literature is also presented.